Effect of sweetener and residue of overripe banana incorporation on physicochemical properties, sensory acceptability and glycaemic index of chocolate cookies - Vern, Ng Yee (2020)
Demand for dietary fibre-enriched and low sugar bakery products is increasing rapidly due to current high incidence of Type 2 diabetes mellitus. Banana is one of the most consumed fruit which provide excellent nutritional health benefits. Meanwhile, overripe banana has been discarded due to its low quality and appearance. Despite its appearance, overripe banana exhibits rich sources of natural sweetener and dietary fibre which could potentially be used as a novel food ingredient to replace added sugar and wheat flour in bakery product. Thus, the study aims to determine the nutritional values, physical properties, sensory acceptability and glycaemic index (GI) value of chocolate cookies formulated with overripe banana sweetener (OBS) as partial replacement (0, 5, 10, 15 and 20%) for table sugar and utilization of overripe banana residue (OBR) as partial replacement (8%) for wheat flour. Results have shown that incorporation of OBR and OBS significantly (p<0.05) increased nutritional values of chocolate cookies. Chocolate cookies formulated with 8% OBR+20% OBS recorded the highest TDF (7.80%) and ash (1.47%) content. Both carbohydrate and sucrose content of chocolate cookies were reduced significantly with increasing level of OBS. In texture profile analyses, an increment in spread ratio as well as a decrease in firmness were shown with increasing levels of OBS in chocolate cookies. Sensory scores for control and 8% OBR-incorporated cookie were not significant difference for all the sensory attributes. Moreover, incorporation of OBS up to 15% produced the highest scores interm of aroma, flavour and overall acceptance. Based on the sensory acceptability results, Three formulations of chocolate cookies (0%, 8% OBR and 8% OBR+15% OBS) were selected for GI testing. It was found that the GI values for 0%-cookie, 8% OBR-cookie and 8%OBR+15%OBS-cookie were 63, 56 and 50, respectively. The results of this study showed that overripe banana can be used as a food ingredient in developing low-GI chocolate cookie.